Implementation of Computer Simulation to Streamline Satellite Motion Learning - Afrizal Mayub (CV. Media Inti Teknologi, 2023)
This study aims to (1) produce a simulation-based satellite motion learning program, (2) describe the effectiveness of simulation-based satellite motion learning, (3) describe the level of effectiveness of satellite motion learning using simulation. The research method consists of; First, software engineering research, namely making satellite motion simulation learning programs based on simulation including: analysis, design, code, and testing. Second, research to see the effectiveness of simulation-based satellite motion simulation learning programs. Sampling using total sampling technique. Based on this, the researchers determined a sample of all Science Masters students in semesters 1 and 3 for the 2021/2022 school year as many as 40 people. The results showed that the satellite motion simulation learning program based on simulation was effective in learning, this can be seen from the N Gain value of 0.60 which is in the high or very effective category. Based on the simulation-based satellite motion learning questionnaire, it is effectively used for satellite motion material. It can be seen from the score obtained at 4.14 (from a scale of 1-5) in the effective category.